Current Trends in the Treatment of Dupuytren Disease in Spain - Sanjuan-Cerveró, Rafael; Gómez-Herrero, Diego; Novoa-Parra, Carlos; Peña-Molina, Fernando; Franco-Ferrando, Nuria (Revista Iberoamericana de Cirugía de la Mano, 2020)
Objective Assessment of the treatment trends of Spanish surgeons in clinical practice by making clinical assumptions in Dupuytren's disease (DD).Material and Method A survey was sent to the members of the Spanish Society for Surgery of the Hand (Sociedad Española de Cirugía de la Mano, SECMA) posing primary and secondary clinical cases. A relationship is established between the selected treatment, the characteristics of the participating surgeons, and the characteristics of the primary clinical cases. Treatment preferences in recurrences are assessed descriptively.Results In total, 127 surveys were answered. 62.2% of the participants had experience with the use of collagenase and were the basis of the analysis. In primary cases, surgeons with more practice time tended to choose collagenase as treatment for DD. Surgeons who reported higher frequency of collagenase use (67.4% vs. 25.7%) were up to 6 times more likely to indicate such treatment. The patient's age under 50 years was the variable with the greatest association strength for the choice of collagenase treatment (OR = 3.8; CI95% 1.9–7.6). In recurrences, among all clinical cases, the most common answer given by the surgeons was partial fasciectomy.Conclusions Partial fasciectomy continues to be the most widely used treatment for DD in Spain. In primary cases, collagenase is an alternative adopted by experienced surgeons, and in treatments for young patients. In recurrences, partial fasciectomy is the preferred technique.Objetivo Valoración de las tendencias de tratamiento de los cirujanos españoles en la práctica clínica mediante la realización de supuestos clínicos en la enfermedad de Dupuytren (ED).Material y Método Se remite una encuesta a los socios de la Sociedad Española de Cirugía de la Mano (SECMA) que plantea casos clínicos primarios y secundarios. Se establece una relación entre el tratamiento seleccionado, las características de los cirujanos participantes y las características de los casos clínicos primarios. Se valoran las preferencias de tratamiento en las recurrencias de modo descriptivo.Resultados En total, 127 encuestas fueron respondidas. El 62,2% de los participantes tenía experiencia con el uso de la colagenasa y fueron la base del análisis. En los casos primarios, los cirujanos con más tiempo de ejercicio mostraron una tendencia a escoger colagenasa como tratamiento para la ED. Los cirujanos que informaban mayor frecuencia de uso de colagenasa (67,4% vs 25,7%) tenían hasta 6 veces más probabilidad de indicar ese tratamiento. La edad menor a 50 años del paciente era la variable con mayor fuerza de asociación para la elección del tratamiento con colagenasa (OR = 3,8; IC95% 1,9–7,6). En las recurrencias, en todos los casos clínicos la respuesta mayoritariamente respondida por los cirujanos fue la fasciectomía parcial.Conclusiones La fasciectomía parcial sigue siendo el tratamiento más utilizado en la ED en España. En los casos primarios, la colagenasa es una alternativa adoptada por cirujanos con experiencia y en tratamientos para pacientes jóvenes. En las recurrencias, la fasciectomía parcial es la técnica preferida.
Keywords: dupuytren disease; faciectomy; collagenase; survey; treatment